PENGARUH MEDIA TANAM TERHADAP PERTUMBUHAN BIBIT JABON MERAH (Anthocephalus macrophyllus (Roxb) Havil) - Yusran Ilyas; Johan A. Rombang; Marthen T. Lasut; Euis F.S. Pangemanan (Universitas Sam Ratulangi, 2015)
ABSTRACT Â This research studied the effects of planting media on the growth of red Jabon (Anthocephalus macrophyllus (Havil) Roxb) seedlings. The objective was to determine the effect of several mixtures of soil, sand, and manure as a planting media for growing seedlings of red Jabon. The research was conducted in two months from April to July 2013, using a completely randomized design (CRD). There are 5 treatments of planting media, namely M1, M2, M3, M4, and M5. Each treatment has 5 replications and each replication was planted with one individual plant. Measured variables were plant height, trunk diameter and leaf number Analysis of variance was done and if there was a significantly different among treatments, a folowing LSD test was carried out. Increments of plant height were significantly different at 63 day after planting,(DAP) whereas increments of trunk diameter were significantly different at 49 DAP. Mixtures of soil, sand and manure showed significantly different effects, and adding sand to the soil with relatively high clay content (> 40%) was important to improve air and water circulation in planting media. Keywords: Media Plant, Red Jabon, Growth